We have to rewrite psychology and psychiatry - Dammen, Philip (Advances in Social Sciences Research Journal, 2015)
Psychology and psychiatry are facing unresolved scientific challenges: We still do not know how the experience of psychological disease is constructed mentally, and what happens mentally when the patients is experiencing a change in treatment, when in the consultation there is a psychological change, and what type of psychological material that can prevent mental change. Diagnoses, as presented in the international diagnostic systems ICD 11 and DSM IV are not sufficiently valid in the sense that they are not precise, controllable expressions of the mental experience of mental torment. Neuro psychology lacks an adequate understanding of the importance of their findings when it comes to understand the psychological and mental processes leading to psychological torment. Moreover, we still do not have a sufficiently scientifically approach to treatment, diagnosing and research on mental illnesses (1). We must rewrite psychology and psychiatry before these subjects will appear to be sufficiently scientific. This article will elaborate on some challenges related to psychology and psychiatry, neuro-psychology and the diagnostic systems ICD 11 and DSM IV faces. At the end, the article will describe some solutions to this situation.